1979
DOI: 10.1002/app.1979.070231207
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature‐vulcanized silicone elastomer: Effect of curing conditions and the nature of filler on mechanical and thermal properties

Abstract: SynopsisLinear poly(dimethylsi1oxane diol) of about 650 D.P. was synthesized by hydrolytic condensation of dimethyldichlorosilane in a saturated solution of sodium chloride. The polymer was then compounded with various fillers, Cab-O-Sil, Dicalite, and titanium dioxide, and cured at room temperature in the presence of tin salt and tri-or tetrafunctional s h e . The tensile strength and elongation of the unfilled rubber were found to be 0.8 kg/cm2 and 320%, respectively. However, Dicalite White (100 phr)-reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…38 Similarly, the duration of UV ageing engenders a proportional increase in hydrolytic reactions and accelerates the scission of the main chain in the elastomer. 34,22,35 It has been found that nano-TiO 2 has a strong ability to resist UV rays. Indeed, the nanoparticles can not only absorb, but also reflect and scatter UV rays due to their refractive index and optical activity.…”
Section: Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Similarly, the duration of UV ageing engenders a proportional increase in hydrolytic reactions and accelerates the scission of the main chain in the elastomer. 34,22,35 It has been found that nano-TiO 2 has a strong ability to resist UV rays. Indeed, the nanoparticles can not only absorb, but also reflect and scatter UV rays due to their refractive index and optical activity.…”
Section: Ageingmentioning
confidence: 99%
“…Another group showed that increased temperature will result in hydrolytic scission at siloxane bonds of the main chain, and oxidation decomposition reactions of the side chain of silicone elastomers. 34 Nano-TiO 2 is a heat-resistant additive and can thus significantly improve the cross-linking reaction temperature of polysiloxane side groups, which in turn improves the heat ageing properties of the silicone elastomer. 22 Furthermore, the thermal oxidation stability of the silicone elastomer is inversely proportional to the size of the additive particles.…”
Section: Ageingmentioning
confidence: 99%
“…Linear polysiloxaediols were prepared by controlled hydrolysis of dichlorosilanes or mixture of dichlorosilanes using satured solution of sodiumchloride in water in 1 : 2 ratio (V/V) at 0.5°C over a period of 2 h. 15,16 The reaction mixture was kept at room temperature for about 24 h, extracted with ether and dried over anhydrous sodiumsulphate. A number of polysiloxanes, that is, PDMS, Poly(vinyl methyl siloxane) (PVMS), Poly(diethylsiloxane) (PDES), and copolymers of the abovementioned polysiloxanes were synthesized for the present study.…”
Section: Synthesis Of Polysiloxanesmentioning
confidence: 99%
“…It is this complex, somewhat poorly defined network structure that largely governs the physical, chemical properties and hence the performance of a silicone elastomer. In the past there has been a reliance on purely empirical additive methodologies in defining structure-property relationships in silicone elastomers for the prediction of materials performance [3][4][5] and beyond the most coarse grain information, the specifics of the network architecture have historically been largely ignored. Today with the ever increasing demands on new materials performance; including better defined, enhanced chemical and engineering properties, improved material reliability and materials lifetimes, there is a need to move beyond basic empirical approaches and instead relate the underlying network structure directly to macroscopic materials behavior.…”
Section: Introductionmentioning
confidence: 99%